Embodiments of Cultural Encounters - Jobs, Sebastian; Mackenthun, Gesa (Cultural Encounters and the Discourses of Scholarship, 2011)
The meeting of members of different cultures, frequently conceptualized in abstract terms, always involves the meeting of human bodies. This volume brings together contributions by scholars of various disciplines that address physical aspects and effects of cultural encounters in historical and present-day settings. Bodies were and are not only markers of cultural identity and difference, endlessly inscribed and represented as the 'body politic' or 'the exotic other'; as battlegrounds of cross-cultural signification and identification bodies are also potential agents of change. While some essays address the elusiveness of the 'real' or material body, forever lost behind a veil of textual and visual representation, others analyze the performative effect of such representations - their function of disciplining colonized bodies and subjects by integrating them into Western systems of cultural signification and scientific classification. Yet, as the volume also shows, formerly colonized people, far from subjecting themselves completely to Western discourses of physical discipline, retain traditional body practices - whether in food culture, religious ritual, or musical performances. Such local reinscriptions escape the grip of Western culture and transform the global semantics of the body.